2019
DOI: 10.22159/ijap.2019v11i4.32988
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Hypoglycemic Study of Isolated Natural Polymer From the Stem of Manilkara Hexandra (Roxb.) Dubard

Abstract: Objective: In the present study, the isolated natural polymer from the stem of Manilkara hexandra and their physiochemical parameters were investigated. It is further involved in hypoglycemic studies. Methods: The gum exudates were screened for phytochemicals, physicochemically analyzed for solubility, pH, total ash, moisture content, acid insoluble ash, water soluble ash, sulfated ash, flow property, and it is characterized by Fourier Transform Infrared analysis (FT-IR), Scanning Electron Microscope (SE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…Studies done by Mallery et al have shown that raspberry bioadhesive (in-situ) has shown a reduction in pre-malignant lesions and antioxidant activity, indicating its better inhibition activity which is also in line with our study; one of the most significant of in-situ formulation in the study is the complete absence of any adverse or deleterious effects in the usage of in-situ gels vs normal gel [ 13 , 17 ].While other studies done by Bansal et al has shown that lycopene along with a combination of polymers (in-situ gel formers such as tween 40, HPMC, etc.) has shown better results due to the increase in patients’ compliance, better adhesive property, reduced effects of UV due to gel application which is also one of the disadvantages of conventional gels [ 2 , 16 ]. Certain studies done by Bignotto et al has shown that the lycopene has a high significant antioxidant property in the dose of 25mg/kg, reducing the risk of cancer and also the anti-inflammatory action in which the injury to the liver cells was reducing the pain [ 1 , 3 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies done by Mallery et al have shown that raspberry bioadhesive (in-situ) has shown a reduction in pre-malignant lesions and antioxidant activity, indicating its better inhibition activity which is also in line with our study; one of the most significant of in-situ formulation in the study is the complete absence of any adverse or deleterious effects in the usage of in-situ gels vs normal gel [ 13 , 17 ].While other studies done by Bansal et al has shown that lycopene along with a combination of polymers (in-situ gel formers such as tween 40, HPMC, etc.) has shown better results due to the increase in patients’ compliance, better adhesive property, reduced effects of UV due to gel application which is also one of the disadvantages of conventional gels [ 2 , 16 ]. Certain studies done by Bignotto et al has shown that the lycopene has a high significant antioxidant property in the dose of 25mg/kg, reducing the risk of cancer and also the anti-inflammatory action in which the injury to the liver cells was reducing the pain [ 1 , 3 ].…”
Section: Resultsmentioning
confidence: 99%
“…Lycopene and Raspberry are known for their antioxidant and anti-cancerous properties. Lycopene, due to its highly lipophilic nature with its protecting mechanism of tissues from the lipid -peroxidation activity, can help to prevent injury, and it is also the most antioxidant among 500 carotenoids present, especially in comparison with beta-carotene, also studies with evidence of pro-oxidative side effects is also seen less in lycopene [ 2 - 32 ]. The lycopene, when consumed directly from tomato, is known as active or bio-lycopene, which has certain anti-inflammatory properties helping to reduce chances of chronic and systemic diseases, the anticancer property of lycopene has proven in various studies to help to reduce even the moderate to advanced stages of cancers and help in the prevention of liver, prostate and other cancers of the body [ 4 - 20 ].…”
Section: Introductionmentioning
confidence: 99%